2021
DOI: 10.2967/jnumed.121.261915
|View full text |Cite
|
Sign up to set email alerts
|

Incidental Findings Suggestive of COVID-19 Pneumonia in Oncologic Patients Undergoing 18F-FDG PET/CT Studies: Association Between Metabolic and Structural Lung Changes

Abstract: Incidental findings suggestive of COVID-19 pneumonia in oncological patients undergoing 18 F-FDG PET/CT studies: association between metabolic and structural lung changes. Short title. PET and CT lung changes on COVID-19.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The increase of FDG uptake in lung lesions with time indicates increasing lung inflammation in the acute stage of COVID-19 infection. COVID-19 Reporting and Data System (CO-RADS) criteria applied to CT findings showed a relation to FDG uptake (SUV max ) in the lung parenchyma in asymptomatic cancer patients ( 45 ). Thornton et al ( 46 ) showed that a lung target-to-background ratio (TBRlung [SUV max /SUV min ]) was strongly correlated with time after infection within 3 weeks after infection, and was higher in the late stage of COVID-19 infection (>1 week to ≤4 weeks after disease onset) than those in the early stage (approximately ≤ 1 week after disease onset) (TBRlung 6.4 vs. 13.7).…”
Section: F-fluorodeoxyglucose Positron Emission Tomography/computed T...mentioning
confidence: 99%
“…The increase of FDG uptake in lung lesions with time indicates increasing lung inflammation in the acute stage of COVID-19 infection. COVID-19 Reporting and Data System (CO-RADS) criteria applied to CT findings showed a relation to FDG uptake (SUV max ) in the lung parenchyma in asymptomatic cancer patients ( 45 ). Thornton et al ( 46 ) showed that a lung target-to-background ratio (TBRlung [SUV max /SUV min ]) was strongly correlated with time after infection within 3 weeks after infection, and was higher in the late stage of COVID-19 infection (>1 week to ≤4 weeks after disease onset) than those in the early stage (approximately ≤ 1 week after disease onset) (TBRlung 6.4 vs. 13.7).…”
Section: F-fluorodeoxyglucose Positron Emission Tomography/computed T...mentioning
confidence: 99%
“…Several studies indicated a 2- to 4-fold increased incidence of interstitial pneumonia detected on 18 F-FDG PET/CT in the latter group during the early phase of the pandemic ( 5 ). Other authors identified a relationship between the structural changes as assessed using the COVID-19 Reporting and Data System and metabolic changes ( 6 ). Albeit informative, such reports did not take into account the temporal kinetics of the disease.…”
mentioning
confidence: 99%